2012
DOI: 10.1258/la.2011.011021
|View full text |Cite
|
Sign up to set email alerts
|

A simple procedure for estimation of total body surface area and determination of a new value of Meeh's constant in rats

Abstract: Precise calculation of total body surface area (TBSA) or premarked surface areas (P-MSAs) is of great importance in many biomedical applications. The aim of the paper was to present a simple procedure of measurement of P-MSAs in small animals and to determine a more accurate Meeh's constant (k), for a commonly used weight range of laboratory rats. A series of 30 Wistar rats, weighing 195 -240 g, were anaesthetized and weighted. The TBSA of each animal was measured using a clear pocket and a planimeter. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 21 publications
0
71
0
3
Order By: Relevance
“…There was no significant difference in the TBSA between these groups (p>0.05). TBSAs were calculated according to Meeh’s formula (TBSA= kW 2/3 ) with a k constant of 9.83 [30]. …”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in the TBSA between these groups (p>0.05). TBSAs were calculated according to Meeh’s formula (TBSA= kW 2/3 ) with a k constant of 9.83 [30]. …”
Section: Resultsmentioning
confidence: 99%
“…For the calculation of the body surface area we used “Meeh’s formula”, which reads as follows: A = K × W 2/3 . Hereby, A represents the body surface area, K an animal specific constant, which was set to 9.83 and W the individual body weight [8]. …”
Section: Methodsmentioning
confidence: 99%
“…One study reported the weekly food consumption for each experimental group, allowing the calculation of an average daily intake of 212 mg of DHA in the ‘Excess DHA’ group (Church, Jen, 2007). In an average-weight lactating rat, assuming a total body surface area (TBSA) of 390 cm 2 using Meeh’s formula (Gouma et al, 2012, Hanson et al, 2001) the “Excess DHA” group’s dose corresponds to approximately 5.4 grams per m 2 . For an adult human the equivalent dose is just over 11 grams of DHA daily (Verbraecken et al, 2006).…”
Section: Resultsmentioning
confidence: 99%